Non-financial analysis in project appraisal – an empirical study - Moutinho, Nuno (2011)
Recent literature has been emphasising the need to take both financial and nonfinancial aspects into consideration when considering capital budgeting decisions. This is to be done since the early stages of project appraisal, and not only when risks become reality. We wanted to know to what extent portuguese companies are aware of the importance of non financial aspects at their project appraisal processes, and, in their practices, what exactly they are doing and considering as more or less important. We looked at financial, strategic, technical, commercial, political, social, environmental, organizational, human resources and project manager factors, and we asked firms: What are the non financial aspects most relevant in their project’s decision?; What are the risk factors considered in each area of analysis?; What procedures they used to minimize the project’s non financial risks?. This allowed us not only to trace the anatomy of Portuguese’s project appraisal methodologies, but also to contribute, through this empirical study, to the body of knowledge in this area. This work also allowed us to differentiate the importance of the different areas of analysis, and the way the analysis is done, according to the characteristics of company and project, company’s administration and project manager.